Impact of Thermal Manipulation of Broiler Eggs on Growth Performance, Splenic Inflammatory Cytokine Levels, and Heat Shock Protein Responses to Post-Hatch Lipopolysaccharide (LPS) Challenge - Mohammad Borhan Al-Zghoul; Seif Hundam; Mohammad Mayyas; David E. Gerrard; Rami A. Dalloul (Animals, 2025)
Thermal manipulation (TM) during embryogenesis is a promising non-pharmacological strategy to enhance physiological resilience in broiler chickens. This study evaluated the impact of thermal conditioning of fertile eggs on growth performance, inflammatory responses, and molecular stress markers following a post-hatch lipopolysaccharide (LPS) challenge. Fertilized eggs (average weight 62 ± 3 g) were obtained from 35-week-old Indian River broiler breeder hens. A total of 720 eggs were randomly assigned to either the control group (n = 360) or the TM group (n = 360), with each group consisting of two replicates of 180 eggs. Control eggs were maintained under standard incubation conditions (37.8 °C, 56% RH), while TM eggs were subjected to elevated temperature (38.8 °C, 65% RH) for 18 h daily from embryonic day 10 to 18. On post-hatch day 15, control and TM groups were administered either saline or LPS via intraperitoneal (IP) injection. Body weight and temperature, internal organ weights, and splenic mRNA expression levels of inflammatory cytokines, toll-like receptors, transcription factors, and heat shock proteins were assessed. TM did not alter hatchability (p = 0.633), but significantly shortened hatch time (p < 0.05) and improved feed efficiency (p < 0.05). While LPS induced marked inflammatory responses in all birds, those subjected to TM exhibited attenuated proinflammatory cytokine expression, enhanced anti-inflammatory signaling, and differential regulation of stress-associated genes, including nuclear factor kappa B (NF-κB), heat shock protein 70 (HSP70), and heat shock factors (HSFs). These findings suggest that TM during incubation promotes a more regulated immune response and improved stress adaptation post-hatch. This approach offers a potential antibiotic-free intervention to enhance broiler health, performance, and resilience under immunological stress.